EXPERIENTIAL MARKETING DALAM PENGALAMAN WISATAWAN PADA PARIWISATA BERKEMAH DI BEDUGUL, BALI - Ni Made Mas Yogiswari; Nyoman Dini Andiani; Luh Putu Triyanti Ariestiana Dewi (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
Experiential marketing is an approach that can optimize tourists’ experiences, particularly in nature-based tourism such as camping. This study aims to analyze the role of experiential marketing in shaping tourist experiences and to identify tourists’ preferences for experience attributes in camping tourism in Bedugul, Bali. A mixed methods approach with a sequential explanatory design was employed, using conjoint analysis to identify preferences and in-depth interviews to explain the quantitative findings. The results indicate that all experiential marketing dimensions (sense, feel, think, act, and relate) have relatively balanced importance, with think and relate emerging as the dominant dimensions. These findings suggest that tourists prefer exploratory activities involving cognitive engagement and collaborative activities that encourage social interaction. The study implies that camping tourism development should emphasize integrated experience-based activities to enhance experience quality and revisit intention.